RESTRUCTURING OF BANKING - CONSEQUENCE TO THE MODERNIZATION OF THE CHANNEL MANAGEMENT - CIURLAU LOREDANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
Any company, any economic-social system tends to develop and make permanent challenges coming from theenvironment in which there are and who is in a continuous transformation. For the banking system in Romania,adaptation to market requirements of the Union Europe is a challenge, but especially a necessity of maintaining a highstandard of professional development, to meet the competition. Getting a free market, in which "the game" is thecompetition, banks must consider very good ratio of profits that wish to obtain them and risks assumed, this report'smost prestigious efficiency of each banks as single entity or of the entire banking system, as a complex entity.In the context of the international financial crisis, the Romanian banking system can be characterized by acomfortable level of solvency and liquidity, you noticed a deterioration in the quality of assets and of posting a modestprofit as a result of stagnating lending activity.In the context of the implementation in Romania of prudential principles of the new Capital Accord (Basel II)with regard to the calculation of capital requirements for credit institutions, the adoption of international financialreporting Standards at the consolidated level, as well as of ensuring convergence prudential reporting requirementswith those of financial reporting surveillance purposes, is taking over in the national law of standardized financialreporting framework on a consolidated basis (FINREP) issued by the Committee of European banking supervisors(CEBS). It is intended to credit institutions that use accounting standards to IFRS in the preparation of consolidatedfinancial reporting.